Understanding satisfying service encounters in retail banking – a dyadic perspective - Nathalie Kania; Thorsten Gruber (2013)
The aim of this study is to expand understanding of satisfying service encounters. In particular, this research study will investigate both parties of the service encounter (customers and frontline employees). A dyadic approach will help to identify whether customer expectations differ from what contact employees believe customers desire from the service encounter. Insights will then lead to a greater understanding of the service encounter as revealed discrepancies in perceptions will not only increase employees' and management awareness, but also provide implications for training and recruitment of employees. An exploratory research study using the well-established laddering interviewing technique was regarded as appropriate as it allows researchers to gain a deeper insight into the research subject. In total, in-depth laddering interviews with 40 respondents (20 customers and 20 frontline employees) were conducted. The findings of this study suggest that customers and employees identified several similar concepts as being important for a successful service encounter such as friendliness, competence, responsiveness, honesty, and communication skills.